ISU-ISU DALAM PENGEMBANGAN HUBUNGAN KAUSAL ANTARA KEPEMIMPINAN ORGANISASIONAL DAN KEEFEKTIFAN ORGANISASIONAL (Fokus Ekonomi, 2009)
In this article, I review major theories of leadership and some empirical research on leadership. Specially I review  the approaches to study organizational leadership, theories of organizational leadership and organizational effectiveness. There are some criteria to be  an effective leader. however if those factors are fulfilled by a leader will  an effective leader lead to an organizational effectiveness? All of these will be discussed in this  paper including issues with the concepts and metodology of leadership and organizational effectiveness.  It is argued here that one of the factors determining organizational effectiveness may be influence by effective leader. However, whether leadership effectiveness lead to organizational effectiveness are also determined by other factors outside control of a leader. Finally, this paper offers some specific implications for further investigation with regard to future research on this topic.